Kompetensi Sosio-Emosional Peserta Didik Berbakat dalam Setting Pendidikan Inklusi - Eka Sakti Yudha; Azni Nurul Fauzia; Nandang Rusmana (Indonesian Journal of Educational Counseling, 2019)
SOCIO-EMOTIONAL COMPETENCIES OF STUDENTS IN THE INCLUSIVE EDUCATION SETTING. The study aims to know the level of emotional-social competencies of gifted students and their implications for the program of appropriate personal-social guidance services to help gifted students improve emotional-social competence. Descriptive research methods were chosen to provide an overview of the phenomena that occur in the field. The research was carried out at Bandung Public High School 4 with the first high school background to carry out inclusive education. The sampling process is done by purposive sampling approach, with the meaning of the sample in the study selected based on predetermined criteria, namely based on the level of intelligence, creativity, and endurance of students who are above the average ability of students in general. The number of samples involved in the study amounted to 39 gifted students of class X in the academic year 2015/2016. Research to measure students' emotional-social competencies in addition to involving personal assessment, also involves peers and teachers who know gifted students. The results showed that the social-emotional competencies of gifted students were generally at the level of competency or were on average abilities based on personal, peer, and teacher ratings. Also, the results of the research were used as the basis for the preparation of a personal social program. The results of the program validation test show that the design of the program is considered feasible to implement.